PENGARUH DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN TAPANULI TENGAH - Ratna Sari Dewi Sigalingging; Nelly Azwarni Sinaga; Sahat Simatupang (CV. ALIM'SPUBLISHING, 2023)
The objectives to be achieved in this study are to determine and analyze the influence of work discipline and career development on employee performance at the Central Tapanuli Regency Transportation Service? The hypothesis in this study is that work discipline and career development have a simultaneous positive effect on employee performance at the Department of Transportation, Central Tapanuli Regency. population amounted to 117 people and a sample of 54 people. The type of data in this study is primary data obtained from field research and literature studies. The results obtained work discipline and career development simultaneously have a positive effect on employee performance at the Department of Transportation of Central Tapanuli Regency, where Fcount (44.747) is greater than Ftable (3, 13) or (44.747 > 3.13) Partially, the work discipline variable has the most dominant effect on employee performance, where the t-count value is 4.056 > t-table value is 2.004. Partially the career development variable has a positive and significant effect on employee performance, where the t-count value is 2.823 > the t-table value is 2.004. The results of calculating the coefficient of determination R Square of 0.554 means that 55.4% of employee performance can be influenced by work discipline and career development. While the remaining 44.6% can be influenced by other factors not discussed in this study.